Stability tools for the spectral-element code Nek5000: Application to Jet-in-Crossflow - Peplinski, A.; Schlatter, Philipp; Fischer, P. F.; Henningson, D. S. (Lecture Notes in Computational Science and Engineering, 2014)
We demonstrate the use of advanced linear stability tools developed for the spectral-element code Nek5000 to investigate the dynamics of nonlinear flows in moderately complex geometries. The aim of stability calculations is to identify the driving mechanism as well as the region most sensitive to the instability: the wavemaker.We concentrate on global linear stability analysis, which considers the linearised Navier–Stokes equations and searches for growing small disturbances, i.e. so-called linear global modes. In the structural sensitivity analysis these modes are associated to the eigenmodes of the direct and adjoint linearised Navier–Stokes operators, and the wavemaker is defined as the overlap of the strongest direct and adjoint eigenmodes. The large eigenvalue problems are solved usingmatrix-freemethods adopting the time-stepping Arnoldi approach.We present here our implementation in Nek5000 with the ARPACK library on a number of test cases.
CRIS-Team Scopus Importer:2023-03-21